2008
DOI: 10.1177/000348940811700505
|View full text |Cite
|
Sign up to set email alerts
|

Office Pulsed Dye Laser Treatment for Benign Laryngeal Vascular Polyps: A Preliminary Study

Abstract: In-office use of the PDL for treatment of vascular polyps may be a safe alternative to phonomicrosurgery. Small polyps seem to show a better response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 12 publications
1
30
1
Order By: Relevance
“…24 A previous study reported successful in-office ablation of hemorrhagic vocal polyps using the pulsed-dye laser. 6 The sizes of vocal lesions regressed significantly in 78% of the study population after 1 to 2 courses of laser treatments; 14% of the patients required surgical polypectomy. Likewise, office-based KTP laser treatment also resulted in significant lesion reduction, usually within 2 postoperative months.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…24 A previous study reported successful in-office ablation of hemorrhagic vocal polyps using the pulsed-dye laser. 6 The sizes of vocal lesions regressed significantly in 78% of the study population after 1 to 2 courses of laser treatments; 14% of the patients required surgical polypectomy. Likewise, office-based KTP laser treatment also resulted in significant lesion reduction, usually within 2 postoperative months.…”
Section: Resultsmentioning
confidence: 91%
“…To ensure complete removal of the vocal polyp during a single procedure, we included only small polyps with a long-axis diameter less than 30% of the vocal fold length visualized on image-processing software (Image J, version 1.44; National Institutes of Health). 6 We excluded nonhemorrhagic and/or wide-based polyps. Among the recruited patients, 20 underwent KTP laser-assisted polypectomy, whereas the other 16 were treated with the KTP laser without endoscopic removal of the polyps.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In‐office laser treatment is indicated for a variety of epithelial lesions of the larynx, including papilloma, granuloma, leukoplakia, dysplasia, Reinke's edema, and vocal fold polyps 46, 48, 51, 52. It has also been used in selected other lesions, such as vascular ectasias and stenosis 47, 48, 53.…”
Section: Use Of the Laser For Treatment Of Laryngeal Conditions In Thmentioning
confidence: 99%
“…Due to delayed lesion regression, the final result should only be expected 4 weeks after the procedure . Smaller polyps tend to respond well to single‐stage in‐office laser procedure, whereas larger polyps may require repeat procedures . The reported complete resolution rates for in‐office KTP and PDL procedures are 85% to 100% and 38% to 100%, respectively.…”
Section: Methodsmentioning
confidence: 99%